Timing and genesis of fractures in the Niobrara Formation, northeastern Front Range and Denver Basin, Colorado - Allen, Cody Lee, author; Erslev, Eric A., advisor; Charlie, Wayne A., committee member; Egenhoff, Sven, committee member; Richter, Bryan, committee member (Colorado State University. Libraries, 2010)
Naturally-occurring fractures in foreland basins, particularly in self-sourced resource plays, are critical to the production of hydrocarbons from low permeability reservoirs. Both shear and extensional fractures commonly cause reservoir anisotropy as well as providing critical tests of tectonic hypotheses. The objective of this research is to determine the mechanisms and timing of naturally-occurring fractures in the upper Cretaceous Niobrara Formation along the northeastern Front Range and in the Denver Basin of the Rocky Mountain Foreland. Previous hypotheses for the origin of fractures within the Denver Basin have focused largely on mechanisms invoking basement reactivation either by vertical block motion or by Laramide subhorizontal shortening. Contrasting hypotheses include multidirectional slip, regional and/or local detachment, and post-Laramide extension in the direction of previous compression. This study analyzes the kinematics, modes and mechanisms of deformation in the Niobrara Formation from fractures examined along the northeastern Front Range and from faults identified in 3D seismic data from the Denver Basin. Surface fracture data collected from 61 locations include minor faults, joints, calcite-filled fractures, and pressure solution stylolites. Subsurface data includes two 3D seismic surveys (Sooner Field and Dana Point) were fault geometries were examined. In outcrops, ideal σ1 analysis of strike–slip and thrust fault data document a subhorizontal Laramide compression with an average attitude of 086°-08°. Normal faults identified through the study are highly variable with an average slip direction of 183°- 73°. Normal dip-slip reactivation of right-lateral shear planes indicates normal faults are younger. Two joint systems are observed throughout the study area with J1 joints averaging 078° and later J2 joints averaging 171°. Subsurface 3D seismic data show listric and planar normal fault sets cut the Niobrara and lower Pierre formations. Calculated fault dip angles at Sooner Field average 8°, and those at Dana Point average 27°. These low fault dip angles suggest layer-parallel detachment, but diverse fault strikes are problematic and suggest multiple slip directions. No basement-to-Cretaceous faults were identified in either volume, casting doubt on basement reactivation hypotheses. Fracture sets in the Niobrara Formation show evidence for four different fracture mechanisms. Initial faulting generated by Laramide subhorizontal compression (086°) was followed by later, but still Laramide, ENE- to E-W-striking J1 splitting joints. Post- Laramide extension is indicated by NNW to N-S-striking J2 joints. Lastly, low-angle listric and planar normal faults in seismic data are interpreted to be post-Laramide. They were probably caused by local detachment, but their mechanisms and timing require further investigation.
Department Head: Sally J. Sutton.